Upaya Pencegahan Cedera Pada Klien Idiopatik Trombositopenia Purpura Di Rsud Pandan Arang - Tri Giarti, Agnis, Endang Zulaicha S , S.Kp (2016)
Background: Idiopathic Thrombocytopenia Purpura is an autoimmune disorder because of platelet antibodies that cause the destruction of platelets early so that the peripheral blood platelets <150,000 / mL. ITP is one reason the incidence of symptomatic bleeding disorder with a range of 3 to 8 per 100,000 children in year. In Pandan Arang Boyolali hospital in 2015 noted there were 11 children out of 1869 children. The actions of defact prevention in ITP is taken to prevent the bleeding. The normal life period of platelet is 7 days, in ITP become 2-3 days. If ITP patients suffered an defact it would be easy bleeding due to platelet acts as a coagulant factor decreases and affects the process of normal hemostasis, usually characterized by petechiae, ecchymosis, easy bruising, bleeding gums, menorrhagia, nose bleeding and hematuria spontaneously. Intracranial bleeding, soft tissue and mucosal bleeding due to trauma can cause mortality. Objectives: The general objective of writing a scientific paper is to determine and implement defact prevention in children with Idiopathic Thrombocytopenia Purpura appropriate nursing standards. The specific objective of this scientific paper is to describe the assessment, data analysis, formulate nursing diagnoses, develop an action plan of nursing, nursing action in accordance with the nursing care plan and evaluate nursing actions for defact prevention in children with Idiopathic Thrombocytopenia Purpura. Results: After action 3x24 hour nursing patients do not get injured. Conclusion: From the actions of defact prevention that have been made in An. A with the implementation of good nursing care for three days then showed that An. A not injured.